Solar Wind Parameters Influencing Magnetosheath Jet Formation: Low and High IMF Cone Angle Regimes - Vuorinen Laura; Hietala Heli; LaMoury Adrian T.; Plaschke Ferdinand (Wiley-Blackwell Publishing, Inc., 2025)
Magnetosheath jets are localized flows of enhanced dynamic pressure that are frequently observed downstream of the Earth's bow shock. They are significantly more likely to occur downstream of the quasi-parallel shock than the quasi-perpendicular shock. However, as the quasi-perpendicular geometry is a more common configuration at the Earth's subsolar bow shock, quasi-perpendicular jets comprise a significant fraction of the observed jets. We study the influence of solar wind conditions on jet formation by looking separately at jets during low and high interplanetary magnetic field (IMF) cone angles. According to our results, jet formation commences when Alfvén Mach number MA ≳ 5. We find that during low IMF cone angles (downstream of the quasi-parallel shock) other solar wind parameters do not influence jet occurrence. However, during high IMF cone angles (downstream of the quasi-perpendicular shock) jet occurrence is higher during low IMF magnitude, low density, high plasma beta (β), and high MA conditions. The distribution of quasi-parallel (quasi-perpendicular) jet sizes parallel to flow peaks at ∼0.3 RE (∼0.1 RE). Some quasi-perpendicular jets formed during high β and MA are particularly small. We show two examples of high β and MA quasi-perpendicular shock crossings. Jets were observed in the transition region, but not deeper in the magnetosheath. A more detailed look into one jet revealed signatures of gyrating ions, indicating that gyrobunched ions near the shock may produce jet-like enhancements. Our results suggest that jets form as part of the quasi-perpendicular shock dynamics amplified by high solar wind MA and β.